Circulación de informaciones y experiencias entre Brasil, Nueva Granada y Venezuela en la formación de la República de Colombia, 1817-1819 (Dossier: El momento colombiano de las repúblicas andinas. Desde el concepto de Colombia hasta el reconocimiento internacional) - Castro, Oscar Javier (2021)
The present article examines the spread of experiences between Portuguese America and the republics of New Granada and Venezuela between 1817 and 1819, a key turning point for the establishment of the first Republic of Colombia. It examines the political ties between Portuguese royalists and republicans from the territories of the Captaincy-General of Venezuela and the Viceroyalty of New Granada in the revolutionary and independence period